القيم السياسية العالمية في الخطاب القرآني للسيد/حسين بدر الدين الحوثي ( العدل نموذجاً) - الحمدي, إبراهيم محمد حسين (Journal of Amran University, 2022)
The study has aimed to elucidate the universal political values in the Quranic discourse for sayyed Hussein B. Al-Houthi (justice as model). It has pinpoint the concept, importance, role of justice and disclosing the negative effects resulting from the weakness of Muslims in setting up fair state and confronting the oppressors. Study has adopted the descriptive approach for reviewing the Quranic discourse in sayyed Hussein B. Al-Houthi sermons, that have been delivered in different occasions Audio recordings and written handouts have stood as references for extracting the universal political values especially the justice ones. The study has also included a lot of findings such as the universality of the Quranic discourse for sayyed Hussein B. Al-Houthi and hoe it has enriched people with the justice values and some universal political values for the purpose of addressing, persuading and submissively adopting its logical reasoning at all times. To added, the inclusivity of Islam has become manifest in its care for serving justice, security and stability of the community through the top political values in the Quranic discourse for all peoples. It is clear of Allah has paid tribute to those values as good examples for ideal community. To sum up, the study has been concluded with the useful recommendation such as boosting and disseminating widely the values, especially, the justice ones, family upbringing, schooling education, role of spiritual guidance of Mosques and targeting media. Thus the best way to improve weakness is to adopt Quran as a guidebook that leads people to the right path and keeps up with the variables and reality of life